Audit committee characteristics and their impact on intellectual capital disclosure: a study of listed manufacturing companies in Sri Lanka / Nimalathasan Balasundaram. - Balasundaram, Nimalathasan (Accounting Research Institute and UiTM Press, Universiti Teknologi MARA, 2019)
In the today's knowledge based economy, intellectual capital (IC) is considered as a strategic asset which determines the value of the company. Different practices of disclosing IC information in annual reports that do not show the real financial position of a company, is a main problem in Sri Lankan companies. The objective of this study was to find out the impact of audit committee characteristics on Intellectual Capital Disclosure (ICD) of listed companies on the Colombo Stock Exchange (CSE) for a period of five- years from 2012/2013 to 2017/2018. The ICD index comprised of 30 items in terms of Relational Capital Disclosure (RCD), Structural Capital Disclosure (SCD) and Human Capital Disclosure (HCD). The data was analyzed using correlations and regression analysis. Most of the Sri Lankan Listed companies disclosed ICD in text, sentences, pictures, tables and graphs in line with the Global Reporting Initiative (GRI) guidelines in their annual reports. ICD was measured by a disclosure index score. The independent variables comprised various forms of audit committee characteristics: audit committee size, frequency of audit committee meetings and audit committee independence. The study confirms that the size of the audit committee and audit committee meetings are important attributes to explain ICD in Sri Lanka. However, the study found a negative significant relationship between ICD and audit committee independence.